2003
DOI: 10.1074/jbc.m304961200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transforming Growth Factor-β Signaling by Protein Inhibitor of Activated STAT, PIASy through Smad3

Abstract: Smads proteins play a key role in the intracellular signaling of the transforming growth factor (TGF)-␤ family of growth factors, which exhibits a diverse set of cellular responses, including cell proliferation and differentiation. In particular, Smad7 acts as an antagonist of TGF-␤ signaling, which could determine the intensity or duration of its signaling cascade. In this study we identified a protein inhibitor of activated STAT (signal transducers and activators of transcription), PIASy, as a novel interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 46 publications
2
84
0
Order By: Relevance
“…HeLa cells were transfected using jetPEI (PolyPlustransfection, Strasbourg, France) according to the manufacturer's instruction. 293T cells were transfected with the standard calcium precipitation protocol [18]. Human embryonic kidney carcinoma cell line, 293T was maintained in DMEM containing 10% fetal bovine serum (FBS) and transfected by the standard calcium precipitation protocol.…”
Section: Methodsmentioning
confidence: 99%
“…HeLa cells were transfected using jetPEI (PolyPlustransfection, Strasbourg, France) according to the manufacturer's instruction. 293T cells were transfected with the standard calcium precipitation protocol [18]. Human embryonic kidney carcinoma cell line, 293T was maintained in DMEM containing 10% fetal bovine serum (FBS) and transfected by the standard calcium precipitation protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Human recombinant TGF-b1 was purchased from Strathmann Biotech GmbH (Hamburg, Germany). Expression vectors, Smad3, TbR-I (T204D), SUMO1, PIASy wild-type (WT), PIASy CA and p3TP-LUC were described previously [4,5,10].…”
Section: Methodsmentioning
confidence: 99%
“…Sumoylation regulates the functions of the target proteins by changing their subcellular localization, protein-protein interactions and/or stability [3]. In a previous study, we demonstrated direct physical and functional interactions between Smad3 and protein inhibitor of activated STATy (PIASy) [4,5]. PIAS proteins were first identified as specific cofactors that inhibit DNA binding of and transcriptional activation by the STAT family of transcription factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…(b) 293T cells in a 12-well plate were transfected with STAT3-LUC (0.4 mg) and/or indicated amounts of WT, D/A or C/S of LMW-DSP2 as described the above. (c and d) Human hepatoma cell line Hep3B and human cervix carcinoma cell line, HeLa, were maintained in DMEM containing 10% FCS (Imoto et al, 2003;Muromoto et al, 2004). Hep3B (c) and HeLa (d) cells in a 12-well plate were transfected with STAT3-LUC (0.5 mg) and/or indicated amounts of WT or D/A of LMW-DSP2 using jetPEI (PolyPlus-transfection).…”
mentioning
confidence: 99%